Pola Pasif dalam Bahasa Indonesi: Suatu Tinjauan Sederhana - Teguh, I Wayan (Humanis; Vol 28 No 2 (2024)DO - 10.24843/JH.2024.v28.i02.p12, 2024)
Indonesian language has several functions. One of the functions of Indonesian language is as a symbol of national identity. The function as a symbol of this national identity is closely related to the statement "language is the mirror  of the nation". From this statement, it is known that the nation's mindset can be understood through the language used. That is, the language used affects the way of thinking of the community. In addition, the language used also affects the way people see and understand the surrounding environment. In connection with this, this article simply reviewed one construction in Indonesian language, namely passive construction. This passive construction is considered important to be discussed (although simply) because it is not highlighted by the actors or agents of an action.